1988
DOI: 10.1002/pen.760280207
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies of polycarbonate‐poly(butylene terephthalate) blends by transmission electron microscopy

Abstract: The morphology of polycarbonate (PC)‐poly(butylene terephthalate) (PBT) blends prepared by melt‐processing in an extruder or a Brabender Plastograph was studied by Transmission Electron Microscopy. Transesterification during blending was avoided by the use of di‐n‐octadecyl phosphite, an efficient transesterification inhibitor. Ruthenium tetraoxide was used to selectively stain the PC fraction. Observation of ultrathin sections revealed the biphasic nature of the blends and the partial compatibility of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 32 publications
2
41
0
Order By: Relevance
“…Delimoy et al, 44 Birley and Chen, 42 Bertilsson et al, 43 Hamilton et al, 40 Hobbs et al, 45 Kim and Burns, 29 Kong…”
Section: The Transesterification Reaction Between Pc and Pbtmentioning
confidence: 99%
See 4 more Smart Citations
“…Delimoy et al, 44 Birley and Chen, 42 Bertilsson et al, 43 Hamilton et al, 40 Hobbs et al, 45 Kim and Burns, 29 Kong…”
Section: The Transesterification Reaction Between Pc and Pbtmentioning
confidence: 99%
“…24,31 As a consequence of this, copolymers act as compatibilisers in these blends, making it difficult to characterise the inherent miscibility of PC and PBT in melt blends. Delimoy et al 44 reported that IR spectroscopy and NMR gave a very coherent picture of the PC-PBT copolyester structure that resulted from an exchange reaction of the aliphatic ester sequences and the aromatic carbonate sequences. Some researchers believe that the transesterification reaction in PC-PBT blends occurs only at temperatures that are greater than the T m of PBT, approximately 220 uC.…”
Section: The Transesterification Reaction Between Pc and Pbtmentioning
confidence: 99%
See 3 more Smart Citations